Development of delayed pulmonary toxicities and transcriptional changes in pre-existing interstitial lung disease mice after partial thoracic irradiation - Jiamei Fu; Xinglong Liu; Yuchuan Zhou; Shengnan Zhao; Liang Zeng; Yan Pan; Jianghong Zhang; Kevin M. Prise; Chunlin Shao; Yaping Xu (Radiation Oncology, 2025)
Abstract Background Lung cancer patients with comorbid interstitial lung disease (LC-ILD) have an increased risk of developing severe or even fatal radiation pneumonitis after thoracic radiotherapy. However, the underlying mechanisms of its pathogenesis are still inconclusive. No approved biomarker or medicine is available to prevent pulmonary toxicities in LC-ILD patients. Appropriate management for them remains a challenge for clinicians due to treatment-related complications. Methods To elucidate the histopathological characteristics and molecular mechanisms responsible for this severe toxicity in vivo, C57BL/6J mice were used to develop different lung injury models, including radiation-induced lung injury (RILI), bleomycin-induced pulmonary fibrosis (BIPF), and severe radiation-related lung injury (sRRLI) murine model. Biopsy examination was performed on hematoxylin and eosin (H&E), Masson’s trichrome, and immunohistochemistry-stained lung tissue sections. Changes in lung function were measured. RNA extracted from mouse lung tissues was sequenced on the Illumina Novaseq platform. Results A severe lung injury model after irradiation was built based on pre-existing ILD mice induced by BLM administration. Enhanced lung injury was observed in the sRRLI model, including higher mortality and pulmonary function loss within six months compared to the mono-treatment groups. Autopsy revealed that bilateral diffuse alveolar damage (DAD) with an overlap of exudative, proliferative, and fibrosing patterns was usually presented in the sRRLI model. The histological phenotypes manifested exudative predominated DAD phase in the early phase and proliferating DAD pattern in the late phase. Bioinformatic analysis showed signaling pathways relevant to immune cell migration, epithelial cell development, and extracellular structure organization were commonly activated in different models. Furthermore, the involvement of epithelial cells and the infiltration of macrophages and CD4 + lymphocytes were validated during extensive lung remodeling in the sRRLI group. Conclusions Delayed effects of significantly declined lung function and high mortality were observed in the sRRLI model. DAD with progressive inflammation and fibrosis in bilateral lungs contributed to severe or even fatal complications after partial thoracic irradiation. The hyperactivation of inflammatory responses was clarified during long-term pulmonary toxicities. More studies are needed to investigate potential strategies to prevent and rescue severe lung complications.